The Effect of Environmental, Social, and Governance (ESG) Disclosure on Tax Avoidance: Firm Size as a Moderating Variable - SARI, PUTRI AYU DEVITA; Machmuddah, Zaky (Pusat P2M Politeknik Negeri Batam, 2026)
This study investigates the impact of Environmental, Social, and Governance (ESG) disclosures on tax avoidance, with firm size acting as a moderating variable. The research focuses on manufacturing companies listed in the Bloomberg ESG database from 2020 to 2023. It employs a quantitative methodology, using regression analysis conducted via SPSS software. Purposive sampling yields 174 observations that meet the established criteria. The empirical findings reveal that all three ESG dimensions—environmental, social, and governance—significantly influence tax avoidance. These results suggest that adopting sustainability principles across various operational areas correlates closely with corporate tax management strategies. Additionally, firm size moderates the relationship between ESG disclosures and tax avoidance, offering deeper insights into tax compliance behaviors among manufacturing firms. The study's implications emphasize the need to integrate ESG practices into corporate governance frameworks. This integration can enhance transparency, accountability, and the effectiveness of tax management.